How audit effort affects audit quality: An audit process and audit output perspective - Tusheng Xiao; Chunxiao Geng; Chun Yuan (China Journal of Accounting Research, 2020)
Using a unique dataset of audit days in China from 2006 to 2011, this paper examines the relationship between audit effort and audit quality from the perspective of audit process and audit output. The results show that audit effort significantly increases the probability of audit adjustments, which inhibits positive earnings management and improves the quality of audited financial statements. We also find that audit effort does not have a significant effect on the issuance of modified audit opinions overall, but that a modified audit opinion is more likely to be issued in the absence of an audit adjustment. Furthermore, we find that the impact of audit effort on audit quality is attenuated when clients are more complex and when audit firms are larger. Collectively, our evidence suggests that audit effort plays an important role in improving audit quality by influencing audit process and audit output. Our study extends the literature on the impact of audit effort on audit quality in emerging markets, and the conclusions have important implications for the improvement of China's audit market efficiency.
Keywords: 650; Audit effort; Audit adjustment; Audit opinion; Audit quality